Pemberdayaan Perempuan dalam Peningkatan Kesehatan Reproduksi melalui Pemeriksaan Organ Reproduksi Mandiri - Farida Yuliani; Fitria Edni Wari; Erfiani Mail (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Community service activity aims to increase the understanding of the people of Gayaman Village and to change behavior regarding early detection of cervical cancer and breast cancer. The method used is health education, discussions, questions and answers. The material given to mothers of childbearing age is about early detection of breast cancer with BSE and early detection of cervical cancer by IVA examination. This activity was attended by 20 women of childbearing age in Gayaman Village, Mojoanyar District in March - June 2020. The results obtained were that the participants were enthusiastic about the education and counseling that had been carried out supported by significant results, where 90% of the participants understood and were able to practice early detection of BSE examination. This activity should be carried out regularly and continuously so that mothers of childbearing age can increase knowledge and increase the coverage of early screening for cervical cancer and breast cancer.